ANALISIS KINERJA DAN PROFESIONALISME GURU SD INPRES KAMPUS UNHAS MAKASSAR - Anwar Enre; Asriandi Asriandi; Ismawati Anwar (El-Fata: Journal of Sharia Economics and Islamic Education, 2023)
This study aims to determine the analysis of performance and Professionalism of Teachers of SD Inpres Unhas Campus Makassar. The research method used is Qualitative Descriptive Research with data analysis and interpretation. Based on the results of research at SD Inpres Kampus Unhas Makassar, teacher performance is seen from pedagogical competence, namely running well; personality competence, namely partly running well; social competence, namely running well; and professionalism competence, namely running well. Teachers, based on their professional competence, are running well, and the correlation between teacher performance and professionalism is that the correlation is going well but not optimally. There are 20 percent that are not optimal, namely because there is no administrative staff and no school committee is formed. So, it is hoped that the correlation between teacher performance and professionalism can be improved and maximized so that it can be applied very well by students at SD Inpres Kampus Unhas Makassar